Cloud Transformation The Public Cloud Is Changing Businesses - Frank, Roland; Schumacher, Gregor; Tamm, Andreas (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2023)
In this book you will learn how the public cloud is significantly changing the cost structures of digital business models and thus existing markets. The relationships between the cloud architectures used, the organization of the company and the price and business models are outlined. These guidelines can be adopted easily in your own company. The authors explain how more and more markets are becoming digital markets and what role marginal costs play. They describe how cloud-based IT is disrupting classic IT enabling small teams to build scalable business models at zero marginal costs with little investment. The economic effects are illustrated by with the help of useful examples. The reader gets an overview of the most relevant factor to improve competitiveness of digital business models. This book is a translation of the original German 1st edition, Cloud-Transformation by Roland Frank, Gregor Schumacher and Andreas Tamm published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2019. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content. The authors Prof. Dr. Roland Frank is the dean of the media and communication management department at the Media Design University of Applied Sciences in Munich. Gregor Schumacher is responsible for the AI and cloud strategy as well as the incubation of new business ideas at Arvato Systems, a subsidiary of the Bertelsmann media company. Andreas Tamm is Lead Enterprise Architect at Arvato Systems and previously worked as a freelance software architect for over 20 years.
Foreword - 1. Do you remember Daimler, RTL and Siemens? - 2. Everything is going digital. - 3. The path to the zero marginal cost economy. - 4. Cloud - automated IT value creation . Cloud IT vs. classic IT - calculation for the controller -- 6. Mastering software as a core competence -- 7. Falling transaction costs and the new network economy -- 8. The cloud transformation -- 9. Cloud transformation - like the public Cloud companies are changing.
Keywords: Management; Business; Management science; Business information services; Management; Business and Management; IT in Business